The Potential of Centong Cactus (Opuntia cochenillifera) as a Remediation Agent for Sidoarjo Mud Polluted Soil with Indicators of Fe Content Reduction and Plant Growth - Alifia Cahyati; Saiful Arifin; M Abror (Universitas Muhammadiyah Sidoarjo, 2022)
Iron (Fe) is one of the heavy metals with high levels in Sidoarjo mud and is toxic to cultivated plants. This study aims to measure the potential of Centong Cactus (Opuntia cochenillifera) as a candidate for soil remediation agent in Sidoarjo Mud contaminated land by using soil Fe uptake and plant growth as indicators. This research was carried out for 3 months from December to March 2022 in the yard of Gebang Village, Sidoarjo District. This study used the correlational regression method to determine the relationship between 0-30% content of Sidoarjo mud with Fe content and various plant growth parameters. The data were statistically processed using regression at the 95% confidence level to determine the significance of the effect and the correlation between the mud content and the decrease in soil Fe content and plant growth. The results showed that there was an increase in soil Fe uptake by plants and a decrease in plant growth with an increase in silt content in the soil of the growing media. O. Cochenillifera has the potential as a candidate for phytoremediation agents that can be applied to areas exposed to Sidoarjo mud, especially for its use to reduce Fe metal levels.